Analisis Langkah-Langkah Kedai Kubo Kopi dalam menjaga Kepuasan Pelanggan - Niki Kusumawardhani Hidayat; Ni Wayan Devi Suryapertiwi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
The trend of drinking coffee as a lifestyle does not only occur abroad. Now in Indonesia, the trend of drinking coffee has also become a habit that continues to increase the number of followers every day. Indirectly, this condition also increases domestic coffee demand. Based on the survey, the average domestic demand for coffee in the period 1984-2008 increased at a rate of 4.32% per year. Meanwhile, the average demand for coffee consumption increases in Asia and the Americas and Europe by 5-8% each year. The trend and increasing demand for coffee also opens up business opportunities to grow coffee. This study uses a qualitative method. This qualitative research uses 6 dimensions of customer satisfaction as the basis of the research. To get the data, it was done by interviewing three core informants in Kubo Kopi. The finding in this study is that the kubo coffee shop not only serves coffee, but also educates its customers who come to their shop. Education about coffee is not only in coffee shops, but baristas and owners also educate coffee plantations in Lampung Province. Thus, old and new customers feel different interests compared to other coffee shops. Besides that, baristas and old and new customers always maintain communication both inside and outside the shop. The education presented at the Kubo Kopi shop is also about manual brew coffee, here customers can also learn latte art for free. Baristas and owners do not hesitate to share knowledge with customers. Finally, their way to make loyal customers is by regularly holding coffee discussions with old and new customers at least once a month.